2021
DOI: 10.1038/s41377-021-00621-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-step-fabricated disordered metasurfaces for enhanced light extraction from LEDs

Abstract: While total internal reflection (TIR) lays the foundation for many important applications, foremost fibre optics that revolutionised information technologies, it is undesirable in some other applications such as light-emitting diodes (LEDs), which are a backbone for energy-efficient light sources. In the case of LEDs, TIR prevents photons from escaping the constituent high-index materials. Advances in material science have led to good efficiencies in generating photons from electron–hole pairs, making light ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…An interparticle distance of MNPs, a key factor to determine the responsive time, is manipulated by the exchange of the ligand attached to MNPs. Moreover, the ligand exchange results in the disorders of MNPs, i.e., disordered NP system that recently gained a great amount of interest (28)(29)(30)(31)(32). The induced disorders become the origin of the highly absorbing dielectric optical properties of the MNP layer, which enables more vivid and marked coloration in reflection compared to structural coloration based on conventional Fabry-Pérot resonators.…”
Section: Introductionmentioning
confidence: 99%
“…An interparticle distance of MNPs, a key factor to determine the responsive time, is manipulated by the exchange of the ligand attached to MNPs. Moreover, the ligand exchange results in the disorders of MNPs, i.e., disordered NP system that recently gained a great amount of interest (28)(29)(30)(31)(32). The induced disorders become the origin of the highly absorbing dielectric optical properties of the MNP layer, which enables more vivid and marked coloration in reflection compared to structural coloration based on conventional Fabry-Pérot resonators.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned research, metasurfaces have shown significant potential in light sources. Applications such as structural light projection [111], enhanced LED light extraction [112], radiation sources of X-ray [113], vacuum ultraviolet light [114], and IR light [115,116] have been demonstrated. The versatile metasurfaces have enabled compact, multifunctional imaging systems.…”
Section: Advanced Devices and Instrumentationmentioning
confidence: 99%
“…14,15 Among the emerging applications, nanoantenna phosphors, i.e., nanoantennas combined with a phosphor, can produce directionally enhanced output. 16 Nanoantenna phosphors are complementary to the nanoantenna LEDs, [17][18][19] where the nanoantenna is attached directly to LEDs. While nanoantennas with an emitter have been a hot topic in nanophotonics, [20][21][22][23][24][25][26][27][28][29][30][31][32] the combination with practical and thick phosphors has been limited so far.…”
Section: Introductionmentioning
confidence: 99%